Produção ecológica de prodigiosina por Serratia marcescens UCP 1549 e aplicação como corante. - Silva, Lucas Albuquerque Rosendo da (2021)
Prodigiosin is a red pigment mainly produced by the Gram-negative bacterium Serratia marcescens, as an intracellular secondary metabolite with wide activity, which can be used in agriculture, fine chemistry and in the pharmaceutical and textile industry. In this work, Serratia marcescens UCP 1549 demonstrated biotechnological potential to produce prodigiosin by converting the renewable substrate corn bran (1%),as the only carbon source and salt solution [KH2PO4, K2HPO4, MgSO4.7H2O and SO4(NH4)2],after 72 h of incubation at 31°C and orbital shaking at 100 rpm. After this period, it was observed a biomass production of 7.24 g/L and red pigment of 1.68 g/L, identified as prodigiosin, through absorbance at 535 nm, Rf of 0.9 in thin layer chromatography (TLC) and functional groups obtained by Fourier Transform Infrared Spectroscopy (FTIR). Prodigiosin showed color stability under different NaCl concentrations and pH values (2-6), however, there was a reduction in color at pH 8, 10 and 12, respectively. The application of the pigment in soap coloring was efficient, suggesting its promising potential as a natural dye in the cosmetic industry. From the ecological production of prodigiosin using corn bran, the effect of substrate concentration and pH on pigment yield was investigated by comparing corn bran and soluble starch as substrates, using a full-factorial design 22. The results obtained indicated higher bacterial growth and production of prodigiosin in the design assays with corn bran, however, the highest yield of prodigiosin occurred at the central point (1% of substrate and pH 7.5). The Pareto diagram showed that both variables had a significant influence on the production of prodigiosin, showing efficiency in the conversion of the alternative substrate. The bioprocess to produce prodigiosin and the dyeing with natural dye in cotton and synthetic fibers are part of the registration with the INPI of Registration of intellectual property.